Penerapan Algoritma Evolution Strategies Dalam Permasalahan VRPTW Pada Optimasi Pendistribusian Pupuk - Lalu Muhammad Ivan Natania; Randy Cahya Wihandika; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Distribution is one of important aspects of marketing. Distribution is a process of transporting goods to consumers by supplier. Without good planning, the distribution process cause loss and damages for the distributor and also the retailers. The loss could be form the cost of fuel and also the time consumed. As for the retailers, goods supply is a crucial element for their business process. To minimize loss, a system is needed to determine the route of delivery with distance and service time as consideration due to limited capacity of container. Vehicle Routing Problem with Time Windows (VRPTW) is the main issue of this research. VRPTW needs great computational processing to deliver good quality of solution. Therefor methods are required to manage and solve the VRPTW issue. Evolution Strategies algorithm is one of many that could be use as a solution of this matters. Based on the experiments, the highest fitness is 0,52421 where the population size is 100, the offsprings size is 10, the generations size is 100, and the SP value is 5. The lowest fitness is 0,45145 where the offspring size is 1, populations size is 100, the generations size is 50, and the SP value is 3.